Market Reactions to Accounting Policy Deliberations: The Inflation Accounting Case Revisited. - Basu, S. (The Accounting Review, 1981)
This article studies the case of market reactions to accounting policy deliberations. The purpose of the article paper is to point out several shortcomings of a study by some researchers and to suggest an alternative framework for testing for potential market reactions to a series of events such as FASB deliberations on inflation accounting. The general research approach employed by researchers is premised on the argument that market reactions to FASB inflation accounting deliberations can be determined, appropriately, by examining the association between abnormal returns of firms for various announcements. Perhaps the most significant limitations stems from the fact that the correlation approach is an awkward, if not inappropriate methodology for application to research problems where the number of variates. The exclusive reliance on that methodology by researchers, therefore, is surprising since there exist alternative research paradigms which, although not free of shortcomings, avoid some problems.